2022
DOI: 10.3389/fcvm.2022.1000260
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and economic impact of coronary artery bypass graft and percutaneous coronary intervention in young individuals with acute coronary syndromes and multivessel disease: A real-world comparison in a middle-income country

Abstract: BackgroundIn recent decades, the world watched a dramatic increase in the incidence of acute coronary syndromes (ACS) among young individuals (≤55 years-old) and a relative decrease in the elderly. The management of ACS in young patients with multivessel disease still needs to be elucidated, as these individuals maintain a long life expectancy.Research QuestionTo compare clinical outcomes and care costs in individuals with premature ACS and multivessel disease undergoing coronary artery bypass graft surgery (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…In participants of the current study, the average monthly expenditure for PCI and CABG were $318.23 and $334.96, respectively. A study conducted in Brazil, a middle-income country, found that direct costs were not different between CABG and PCI patients with a median of $630.72 and $672.29, respectively [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In participants of the current study, the average monthly expenditure for PCI and CABG were $318.23 and $334.96, respectively. A study conducted in Brazil, a middle-income country, found that direct costs were not different between CABG and PCI patients with a median of $630.72 and $672.29, respectively [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Os custos diretos para CRVM e ICP foram equivalentes (Int$ 3.141 [IIQ: 15.392]/ano e Int$ 3.348 [IIQ: 17.884]/ano), enquanto o custo por perda de produtividade laboral foi mais alto no grupo ICP (Int$ 4.511 [IIQ: 18.062]/ano e Int$ 3.578 [IIQ: 13.198]/ano, p = 0,049) em comparação ao grupo CRVM. 134 …”
Section: Utilização E Custo Da Atenção à Saúdeunclassified
“…In addition to amplifying ACS-related reduction in quality of life and life expectancy, yACS also carries a heavy economic burden by reducing work capacity in early adulthood [3][4][5] .Young individuals with ACS are more likely to be men, smokers, obese, sedentary or to present familialcombined hyperlipidemia, and they more frequently consume cocaine or androgenic anabolic steroids than older ACS patients 6,7 . Furthermore, compared with older individuals, those with yACS have a higher proportion of traditional cardiovascular risk factors out of control 7,8 . This setting of frequent uncontrolled risk factor among yACS triggers a relevant economic impact 8 .…”
mentioning
confidence: 99%